Probucol Suppresses Enterocytic Accumulation of Amyloid-β Induced by Saturated Fat and Cholesterol Feeding - Pallebage-Gamarallage, Menuka; Galloway, Susan; Takechi, Ryusuke; Dhaliwal, Satvinder; Mamo, John (Springer, 2011)
Amyloid-β (Aβ) is secreted from lipogenic organs such as intestine and liver as an apolipoprotein of nascent triacylglycerol rich lipoproteins. Chronically elevated plasma Aβ may compromise cerebrovascular integrity and exacerbate amyloidosis—a hallmark feature of Alzheimer’s disease (AD). Probucol is a hypocholesterolemic agent that reduces amyloid burden in transgenic amyloid mice, but the mechanisms for this effect are presently unclear. In this study, the effect of Probucol on intestinal lipoprotein-Aβ homeostasis was explored. Wild-type mice were fed a control low-fat diet and enterocytic Aβ was stimulated by high-fat (HF) diet enriched in 10% (w/w) saturated fat and 1% (w/w) cholesterol for the duration of 1 month. Mice treated with Probucol had the drug incorporated into the chow at 1% (w/w). Quantitative immunofluorescence was utilised to determine intestinal apolipoprotein B (apo B) and Aβ abundance. We found apo B in both the perinuclear region of the enterocytes and the lacteals in all groups. However, HF feeding and Probucol treatment increased secretion of apo B into the lacteals without any change in net villi abundance. On the other hand, HF-induced enterocytic perinuclear Aβ was significantly attenuated by Probucol. No significant changes in Aβ were observed within the lacteals. The findings of this study support the notion that Probucol suppresses dietary fat induced stimulation of Aβ biosynthesis and attenuate availability of apo B lipoprotein-Aβ for secretion.